A study to find the correlation between 24-hour urinary protein and spot urinary albumin to creatinine ratio and to determine the accuracy of spot urinary albumin to creatinine ratio as an indicator to detect proteinuria and its use as a rapid alternative test over 24-hour urinary protein in preeclamptic women - Mahesh, Sowmya; Borgohain, Deepa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Preeclampsia is a multisystem endothelial disease leading to glomeruloendotheliosis with endothelial leak causing significant proteinuria. It is associated with high maternal and fetal risks and fetomaternal morbidity and mortality. Spot urinary albumin to creatinine ratio (ACR) leads to earlier detection of glomerular damage leading to prompt management of preeclamptic patients. To determine the accuracy of Spot Urinary ACR as an indicator to detect proteinuria and its use as a rapid alternative test over 24-hour urinary protein in women with Preeclampsia and to find the correlation between the two. Methods: Spot urinary ACR was measured in 70 consecutive patients with preeclampsia in Assam Medical College, Dibrugarh. The best cut-off value to differentiate between significant and insignificant proteinuria was calculated. The mean, standard deviation and range of various parameters were computed and various statistical tests were used. The Area under the curve and ROC curve were plotted. Results: The best cut-off value to differentiate significant and insignificant proteinuria was calculated as 291.9 mg/g beyond which adverse fetomaternal outcomes and complications were seen. The correlation coefficient between 24-hour urinary protein and spot urinary albumin to creatinine ratio was 0.922 highly significant. The area under the curve was found to be 0.98 with a standard error of 0.0155 which implied that the discriminant ability of spot urinary ACR to differentiate significant proteinuria from insignificant proteinuria in patients with preeclampsia was found to be 98%. Similar studies mentioned in the table below showed a good correlation between 24-hour urinary protein estimation and spot urinary ACR. Conclusions: Compared with 24-hour urinary protein excretion, spot urinary ACR is a simple and accurate indicator of significant proteinuria and helps to detect fetomaternal outcomes in preeclamptic women which may lead to prompt management to reduce fetomaternal complications.